Stochastic Consensus of a Class of Continuous-Time Multi-Agent Systems with a Leading Agent. (30th March 2016) - Zhu, Qiuguo; Wu, Jun; Xiong, Rong
A stochastic consensus problem is studied for a class of continuous-time multi-agent systems with a leading agent. The systems have a switching coupling topology driven by a homogeneous Markov process. The unknown coupling functions among agents are nonlinear or even discontinuous. Under some constraints on the unknown coupling functions, a sufficient condition is provided to guarantee stochastic consensus. The condition is in the form of a linear matrix inequality, which is computationally convenient.